Pola Pembinaan Prestasi Olahraga Beladiri Wushu Koni Kabupaten Semarang Di Masa Pandemi Covid 19 - Gandung Nurwanda (YLPK Mahardhika, 2021)
The purpose of this study is to describe the pattern of fostering the sports achievement of wushu martial arts in the KONI Kabupaten Semarang during the Covid 19 pandemic. This study uses descriptive qualitative methods. Sources of data in this study consisted of athletes, coaches, and administrators of the KONI Kabupaten Semarang. The data collection technique is an interview technique. The data analysis technique used an interactive analysis model. The results showed that the pattern of fostering the sports achievement of the KONI Kabupaten Semarang uses a talent scouting system, which means the process of scouting the talents of athletes from the recruitment stage to the final stage of coaching. The spirit of training and the athletes' efforts to achieve optimal performance are supported by the quality of the coaches which are already good, because all coaches have coach certification, and the training programs provided are in the good category. The management organization in good criteria is seen from the attention of the administrators to the athletes, and the management of Wushu martial arts. The facilities and infrastructure owned are included in the criteria both in terms of the completeness and quality of the existing facilities and infrastructure. Funding for the implementation of Wushu martial arts performance coaching is included in the criteria both seen from the source of funding and how to allocate funds for the coaching process. The conclusion obtained is that the pattern of fostering wushu martial sports achievements at the KONI Kabupaten Semarang is running well, has been programmed, tiered, and sustainable.